ANALISIS PENGENDALIAN WAKTU SELESAI PROYEK DENGAN MENGGUNAKAN METODE FAST-TRACK (STUDI KASUS : PEMBANGUNAN MASJID PEMKAB DELI SERDANG) - Novia Sari (Jurnal Teknik Sipil USU, 2019)
ABSTRACK  Projects can be said to be completed if the project work has arrived at a predetermined point which is no longer possible to do the next job. There are several types of scheduling that can be done, and one of them uses the fast track method. Fast Track itself is a project completion system that is faster than the planned time by using more efficient methods so that it can reduce the time of project implementation. The fast track method can shorten implementation time and save project costs compared to traditional (conventional) methods that rely on a rigid sequence of activities. At present the application of the fast track method can help planning so that the implementation is on time or in accordance with the desired completion time. The results of the study showed that the initial implementation time was 420 days while the fast track method was 385 days, then by using the fast track method there is an acceleration of 35 days from the time of the initial implementation of the initial planning  Keywords: completion of the project, planning, control, Fast Track method